Molecular and physiological responses of recalcitrant Indica rice to pluronic F-68 during callus regeneration - Kok, Andrew De Xian (2021)
Pluronic F-68 (PF-68) is a non-ionic surfactant commonly used as a growth additive in plant tissue culture. However, there are limited studies on the effects of PF-68 in rice. Therefore, this study was undertaken to evaluate the growth promoting effects of PF-68 on callus proliferation, shoot growth and root growth of recalcitrant MR219 rice. MR219 calli and shoot apices were cultured on Murashige and Skoog (MS) medium supplemented with different concentrations [0 %, 0.02 %, 0.04 %, 0.06 %, 0.08 %, 0.10 % (v/v)] of PF-68. Calli grown on MS medium supplemented with 0.04 % PF-68 improves callus proliferation rate by 1.59-fold (fresh weight), 1.24-fold (dry weight) and enhanced root induction from the calli by 1.29-fold. However, increasing frequency of brown and black calli was observed when 0.10 % PF-68 was used. In shoot growth study, PF-68 did not exhibit any growth promoting effects on MR219. On the other hand, optimum root growth was observed in shoot apices treated with 0.04 % PF-68. Growth of the roots was increased significantly by 1.43-fold and root length by 1.19-fold compared to the control. In order to evaluate the underlying mechanism of growth promoting effects of PF-68, callus was used as a study model and three different concentrations were selected for further analysis; namely control, optimum (0.04 % PF-68) and high concentration (0.10 % PF-68). Biochemical analyses revealed high accumulation of sugar (1.77 mg/mL) and protein (0.17 mg/mL) contents in 0.04 % PF-68-treated calli. Similarly, quantitative realtime reverse transcription polymerase chain reaction (RT-qPCR) also revealed that high expressions of sucrose synthase (2.65-fold) and NADH-dependent glutamate synthase (1.86-fold) transcripts, which correlated with the high sugar and protein contents detected in 0.04 % PF-68-treated calli. Besides, calli treated with high concentration of PF-68 (0.10 %) recorded increased accumulation of phenolic (0.74 mg/mL), flavonoid (0.08 mg/mL), and phenylalanine ammonia lyase (PAL) activity (0.28 U/μg protein), which implied enhanced secondary metabolites biosynthesis in 0.10 % PF-68-treated calli. Further gene expression quantification also recorded an increased in 4- coumarate:CoA ligase 3 (1.28-fold) and chalcone-flavonone isomerase (1.65-fold) transcripts in 0.10 % PF-68-treated calli. Subsequent biochemical analyses revealed high H2O2 activity (0.10 mg/mL), malondialdehyde content (0.024 U/μg protein) and peroxidase activity (0.15 U/μg protein) in 0.10 % PF-68-treated calli. Consistently, high expression level of ascorbate peroxidase (1.61-fold) was observed in 0.10 % PF-68-treated calli, suggesting activation of the plant defense mechanism against increasing stress induced from high concentration of PF-68. However, a decrease in esterase activity (34,204.50 nmol/ng protein) was recorded at 0.10 % PF-68, which implied increasing stress induced by PF-68 to trigger programmed cell death. Further comparative proteomic analysis revealed an upregulation of alpha-amylase and NADH-dependent glutamate synthase proteins detected in 0.04 % PF-68-treated calli. This indicates PF-68 enhances callus proliferation via enhanced carbon and nitrogen metabolism in 0.04 % PF-68-treated calli. In contrast, upregulation of PAL protein was detected in 0.10 % PF- 68-treated calli. These results suggest that secondary metabolite biosynthesis was enhanced in 0.10 % PF-68-treated calli. In addition, nutrient ion analysis revealed an increased uptake of K, Mg, Ca, Fe, Zn, Cu and Mn ions were also observed in 0.04 % PF-68-treated calli. Among these nutrient ions, K had the highest increment of nutrient content detected in 0.04 % PF-68-treated calli. The increased K uptake plays an important role in plant growth and development such as protein synthesis and carbohydrate metabolism. Overall, the results from this study showed that the growth promoting effects of PF-68 on in vitro MR219 rice cultures were concentration dependent. Taken together, at optimum concentration, PF-68 improves recalcitrant rice callus proliferation via enhanced sugar metabolism, amino acid biosynthesis and nutrient uptake which are crucial towards plant growth and development. However, at high concentration, PF-68 induces stress response in plant as evidenced by the increased secondary metabolites content, H2O2 activity, malondialdehyde content and peroxidase activity. Hence, optimum concentration of PF-68 has potential to be utilized as an additive for plant growth and development in tissue culture of rice cultivars.